Pengaruh Penggunaan Media Pembelajaran Berbasis Video dalam Meningkatkan Motivasi dan Hasil Belajar Bahasa Arab Peserta Didik Kelas XI MAN 1 Barru - Muhabba, Iqrail; Herdah; Kaharuddin; Darmawati; Halim (Jurusan Pendidikan Bahasa Arab, 2025)
This thesis discussed the use of video-based learning media to enhance motivation and learning outcomes in Arabic among students of class XI at MAN 1 Barru. This research adopted an associative research design with a quantitative approach. The population of this study consisted of 101 students of class XI, and a sample of 78 students was selected. Data were collected through observations and questionnaires. The collected data were analyzed using statistical tests with SPSS version 24. The findings of this study indicated that: 1) Video-based learning media for Arabic among students of class XI at MAN 1 Barru fell under the moderate category. 2) The motivation to learn Arabic among students of class XI at MAN 1 Barru was in the moderate category. 3) The learning outcomes in Arabic among students of class XI at MAN 1 Barru were in the moderate category. 4) There was a significant influence of video-based learning media on motivation and learning outcomes in Arabic among students of class XI at MAN 1 Barru. Based on the output of the SPSS Test of Between Subject Effects, univariate ANOVA was used to examine the influence of each factor on the dependent variable. The significant F-test values were used to test this relationship. The F-test value for the relationship between the use of video-based learning media (X) and Learning Motivation (Y1) was 3.083 with a significance value of 0.000 < 0.05. Meanwhile, the F-test value for the relationship between the use of video-based learning media (X) and Learning Outcomes (Y2) was 2.896 with a significance value of 0.010 < 0.05. This indicated that there was a difference in the use of video-based learning media in terms of motivation and learning outcomes in Arabic among students of class XI at MAN 1 Barru.